2022
DOI: 10.1186/s13014-022-02054-x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of therapeutic outcome and role of reirradiation in patients with radiation-induced glioma

Abstract: Background We sought to clarify the optimal follow-up, therapeutic strategy, especially the role of reirradiation, and the diagnostic impact of isocitrate dehydrogenase (IDH) 1 and 2 mutation status in patients with radiation-induced glioma (RIG). Methods We retrospectively reviewed the clinical characteristics and treatment outcomes of 11 patients with high-grade glioma who satisfied Cahan’s criteria for RIG in our database during 2001–2021. IDH 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…However, there have been just a handful of reports about the fatality of radiation necrosis during the survival periods of patients after re-RT for RIMG. 23 Such radiation necrosis has been reported in patients with high-grade gliomas or other brain tumors, who survived for a longer period, 7 but not in patients with GCTs. In general, the tolerance to re-RT increased with an increasing time to re-RT and a decreasing initial radiation dose.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…However, there have been just a handful of reports about the fatality of radiation necrosis during the survival periods of patients after re-RT for RIMG. 23 Such radiation necrosis has been reported in patients with high-grade gliomas or other brain tumors, who survived for a longer period, 7 but not in patients with GCTs. In general, the tolerance to re-RT increased with an increasing time to re-RT and a decreasing initial radiation dose.…”
Section: Discussionmentioning
confidence: 96%
“…Previous reports recommended re-RT in addition to chemotherapy for RIMG. 7 , 23 A study regarding the role of RT in the treatment of patients with RIMG showed that 1-, 2-, and 5-year overall survival rates were 58.9%, 20.5%, and 6.8%, respectively, in the patients undergoing re-RT, which were higher than those in patients not undergoing re-RT (15.1%, 3%, and 0%, respectively). 7 Another article showed that the median progression-free survival time of patients treated with re-RT and chemotherapy tends to be longer than that of patients who received chemotherapy alone (17.0 versus 8.1 months).…”
Section: Discussionmentioning
confidence: 99%
“…RT improves the outcome of pediatric patients but is also associated with long-term risks. These can be observed especially in children with long-term follow-up 1 . One of the most serious risks is the development of radiation-induced gliomas (RIGs), which have been described in patients primarily treated mainly for acute lymphoblastic leukemia (ALL) and central nervous system (CNS) malignancies by cranial RT 2 , 3 .…”
Section: Introductionmentioning
confidence: 95%
“…However, significant progress is now being made in their molecular biological characterization 6 , 7 . Unlike their primary counterparts, RIG do not usually carry the typical mutations in the Histon3, IDH1/2 or BRAF genes 1 , 8 , 9 . Based on methylation profiling, RIG mostly clustered within the GBM_pedRTK1 methylation group.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation